2019
DOI: 10.1155/2019/6210240
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Iron Using SiO2 Nanoparticles Extracted from Rice Husk Ash

Abstract: In this work, SiO2 nanoparticles were prepared by the sol-gel method after sodium silicate was extracted from rice husk ash (RHA) under various experimental conditions such as types of acids, NaOH concentration, dissolved time, and temperature and used for removal of Fe2+ ions from aqueous solutions. The extracted SiO2 was morphologically and chemically characterized and showed a surface area of 78 m2/g and uniform pores of 2.71 nm, offering high adsorption capacity for Fe2+ ions. The influence of pH, contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…SiNPs were generated from rice husk ash, and physicochemical properties were characterized by the Fourier transform infrared spectroscopy (FTIR), scanning electronic microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). e results showed that the absorption bands were obtained at 1069 and 794 cm −1 , which corresponded to the symmetric and asymmetric components of Si-O-Si variation as shown in Figure 1(a) [28]. e irregular shapes of SiNPs with a diameter of around 50 nm were achieved by SEM as depicted in Figure 1(b).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…SiNPs were generated from rice husk ash, and physicochemical properties were characterized by the Fourier transform infrared spectroscopy (FTIR), scanning electronic microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). e results showed that the absorption bands were obtained at 1069 and 794 cm −1 , which corresponded to the symmetric and asymmetric components of Si-O-Si variation as shown in Figure 1(a) [28]. e irregular shapes of SiNPs with a diameter of around 50 nm were achieved by SEM as depicted in Figure 1(b).…”
Section: Resultsmentioning
confidence: 91%
“…e gel obtained was then dispersed in ethanol, washed with distilled water (three times), and dried at 110°C for 2 h to remove remaining surfactants. e SNPs synthesized were stored in desiccator for further characterizations [28].…”
Section: Extraction Process Of Sinpsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they have several drawbacks such as high costs, time-consuming to perform, complicated in operation, and low efficiency in processing [8]. Therefore, adsorption-based methods are the most useful and economical among the various techniques mentioned above due to benefits such as high adsorption capacity, low cost and an environmentally friendly approach [9,10].…”
Section: Introductionmentioning
confidence: 99%